Revision der brevilabris Horn-Gruppe der Collyrini (Coleoptera: Cicindelidae). - Mandl, Karl Ferdinand jun. (Contributions to Entomology = Beiträge zur Entomologie, 1975)
A close examination of Neocollyris brevilabris Horn led to a revision of the brevilabris-group. The following species and subspecies are grouped as a genus Protocollyris and described: brevilabris Horn, weyersi (Horn) bona species, weyersi bryanti sspec. nov., longiceps spec. nov., philippinensis Mandl and mindanaoensis Mandl. Nomenclatural Acts longiceps Mandl, 1975 (Protocollyris), spec. n. bryanti Mandl, 1975 (Protocollyris weyersi), sspec. n.